Exterior orientation of CBERS-2B imagery using multi-feature control and orbital data - Marcato Junior, J.; Tommaselli, A. M G [UNESP] (Elsevier, 2013)
The major contribution of this paper relates to the practical advantages of combining Ground Control Points (GCPs), Ground Control Lines (GCLs) and orbital data to estimate the exterior orientation parameters of images collected by CBERS-2B (China-Brazil Earth Resources Satellite) HRC (High-resolution Camera) and CCD (High-resolution CCD Camera) sensors. Although the CBERS-2B is no longer operational, its images are still being used in Brazil, and the next generations of the CBERS satellite will have sensors with similar technical features, which motivates the study presented in this paper. The mathematical models that relate the object and image spaces are based on collinearity (for points) and coplanarity (for lines) conditions. These models were created in an in-house developed software package called TMS (Triangulation with Multiple Sensors) with multi-feature control (GCPs and GCLs). Experiments on a block of four CBERS-2B HRC images and on one CBERS-2B CCD image were performed using both models. It was observed that the combination of GCPs and GCLs provided better bundle block adjustment results than conventional bundle adjustment using only GCPs. The results also demonstrate the advantages of using primarily orbital data when the number of control entities is reduced. © 2013 International Society for Photogrammetry and Remote Sensing, Inc. (ISPRS).
Keywords: Orientation; Pushbroom; Satellite; Straight lines; Triangulation; Bundle block adjustments; China-brazil earth resources satellites; Exterior orientation; Exterior orientation parameters; Ground control points; High resolution camera; Crystal orientation; Mathematical models; Rock mechanics; Satellites; Sensors; CCD cameras; estimation method; mathematical analysis; numerical model; orientation; remote sensing; resolution; satellite data; satellite imagery; triangulation; Brazil; China